CON4EI: Selection of the reference chemicals for hazard identification and labelling of eye irritating chemicals. (October 2017) - Adriaens, E.; Alépée, N.; Kandarova, H.; Drzewieckac, A.; Gruszka, K.; Guest, R.; Willoughby, J.A.; Verstraelen, S.; Van Rompay, A.R.
Abstract: Assessment of the acute eye irritation potential is part of the international regulatory requirements for testing of chemicals. In the past, several prospective and retrospective validation studies have taken place in the area of serious eye damage/eye irritation testing. Success in terms of complete replacement of the regulatory in vivo Draize rabbit eye test has not yet been achieved. A very important aspect to ensure development of successful alternative test methods and/or strategies for serious eye damage/eye irritation testing is the selection of appropriate reference chemicals. A set of 80 reference chemicals was selected for the CEFIC-LRI-AIMT6-VITO CON4EI (CONsortium for in vitro Eye Irritation testing strategy) project, in collaboration with Cosmetics Europe, from the Draize Reference Database published by Cosmetics Europe based on key criteria that were set in their paper ( e.g. balanced by important driver of classification and physical state). The most important goals of the CON4EI project were to identify the performance of eight in vitro alternative tests in terms of driver of classification and to identify similarities/differences between the methods in order the build a successful testing strategy that can discriminate between all UN GHS categories. This paper provides background on selection of the test chemicals. Highlights: Selection of reference chemicals for eye irritation/serious eye damage is proposed. Chemicals were selected from the Draize Reference Database based on key criteria. Chemicals were balanced by important driver of classification and physical state. The set was composed of 80 reference chemicals.